Halal Tourism Short Course-Based Mentoring to Strengthen the Capacity of Local Tourism Groups - Eko Andy Saputro; Alfet Robi Nur Muhammad; Galuh Dwi Purwasih (Universitas Nurul Jadid, 2026)
The Southern Coastal Route (Jalur Lintas Selatan/JLS) of Tulungagung has significant potential for community-based coastal tourism; however, limited managerial capacity among local tourism awareness groups (Pokdarwis) hinders its development. Key challenges include low access to tourism training, limited halal tourism literacy, and weak digital branding skills, which affect service quality, Muslim-friendly readiness, and destination competitiveness. This program aimed to strengthen Pokdarwis capacity through a participatory Halal Tourism Short Course using the Asset-Based Community Development (ABCD) approach. The program was implemented through intensive mentoring, thematic workshops, Focus Group Discussions (FGDs), participatory asset mapping, and pre–post evaluations. The results show measurable improvements, with participants’ managerial understanding increasing by 35%, halal tourism literacy by 40%, and digital branding competency by 38% based on pre–post test scores. Participants were able to design halal tourism service plans, identify Muslim-friendly services, and optimize digital platforms for destination promotion.Furthermore, 70% of participants demonstrated readiness to develop halal-based tourism products, including halal culinary services, Muslim-friendly homestays, and Islamic educational tourism packages. The novelty of this program lies in integrating ABCD-based empowerment, halal tourism literacy, and digital branding into a structured participatory short-course model tailored for coastal communities. This approach contributes to strengthening local tourism governance and supports sustainable, inclusive, and competitive halal tourism development along the JLS corridor.